2007
DOI: 10.1073/pnas.0704091104
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral improvement in a primate Parkinson's model is associated with multiple homeostatic effects of human neural stem cells

Abstract: Stem cells have been widely assumed to be capable of replacing lost or damaged cells in a number of diseases, including Parkinson's disease (PD), in which neurons of the substantia nigra (SN) die and fail to provide the neurotransmitter, dopamine (DA), to the striatum. We report that undifferentiated human neural stem cells (hNSCs) implanted into 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-treated Parkinsonian primates survived, migrated, and had a functional impact as assessed quantitatively by behavioral im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
275
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 319 publications
(292 citation statements)
references
References 39 publications
15
275
1
1
Order By: Relevance
“…To date there is little evidence that new neurons derived from NSCs can regenerate circuitry. A more likely role for NSCs in transplantation is to act as support cells providing neurotrophic factors and reversing some of the damage caused by injury and disease [Redmond et al, 2007]. For example, some researchers have bypassed the use of NSCs altogether and used GDNF implants as a means to treat Parkinson's disease [Patel et al, 2005].…”
Section: Clinical Application's Of Nscsmentioning
confidence: 99%
“…To date there is little evidence that new neurons derived from NSCs can regenerate circuitry. A more likely role for NSCs in transplantation is to act as support cells providing neurotrophic factors and reversing some of the damage caused by injury and disease [Redmond et al, 2007]. For example, some researchers have bypassed the use of NSCs altogether and used GDNF implants as a means to treat Parkinson's disease [Patel et al, 2005].…”
Section: Clinical Application's Of Nscsmentioning
confidence: 99%
“…The number of neural stem cells (NSCs), for example, that differentiate into mature well-integrated neurons, and the lengthy time this process requires, are usually insufficient to account for the improvement. Although it is becoming recognized that grafted NSCs interact with-indeed, sustain, rescue, or protect-endogenous imperiled neurons in vivo (1)(2)(3), the underlying mechanisms are poorly characterized. Although, in some cases, we and others have attributed this action to the release of diffusible cytokines from NSCs (1,2), this mechanism alone is inadequate for explaining all cases (3).…”
mentioning
confidence: 99%
“…(iv) Given that these were severestage Parkinsonian primates (Hoehn and Yahr stage 5 equivalent), will the results be more robust in earlier-stage patients if the cells can protect and repair more of the dopamine nigrostriatal system? Redmond et al (2) reported no dyskinesias, tumors, deformations, or overgrowth in the transplanted primates. There also did not appear to be inappropriate stem cell migration.…”
mentioning
confidence: 99%
“…In a National Institutes of Health-funded study reported in this issue of PNAS, Redmond et al (2) have now taken the first step toward demonstrating the successful use of fetal stem cells in a primate Parkinson's model.…”
mentioning
confidence: 99%
See 1 more Smart Citation